Evaluation of conjunctival bacterial flora in a herd of goats in the Midwestern United States. (18th January 2016) - Meekins, Jessica M.; Apley, Michael D.; Lubbers, Brian; Peddireddi, Lalitha; Rankin, Amy J.
Abstract: Objective: To identify conjunctival bacterial flora in healthy adult and newborn kid goats in the Midwestern United States and to compare vaginal and ocular surface flora in dam‐kid pairs. Animals studied: Thirty mixed‐breed (crosses between Boer, Kiko, and Syfan Spanish) goats, 20 adult does and 10 newborn kids. Procedures: One eye of 15 adult goats ( n = 15 eyes) and 5 kids ( n = 5 eyes) was randomly selected. A subset of 5 adults ( n = 10 eyes) and 5 kids ( n = 10 eyes) underwent bilateral sampling. Each recently kidded dam's vaginal canal ( n = 10) was also sampled. Two swabs were collected from each sample site for aerobic bacterial culture and Mycoplasma and Chlamydia spp. PCR. Results: Of the animals with positive cultures, Staphylococcus and Streptococcus were the most common bacterial genera from the conjunctival sac of adult (16/17; 94%) and kid (5/5; 100%) goats; three adults and 5 kids had no growth of bacteria on aerobic culture. Moraxella bovoculi was the most common single bacteria in adults, in 9 eyes (36%) of 8 animals (40%). Staphylococcus equorum was identified in all 5 kids with positive cultures. Mycoplasma sp. DNA was detected in 7 animals. Chlamydia sp. DNA was not detected in any sample. Four of 10 dam‐kid pairs had identical bacteria isolated from the dam's vaginal sample and the kid's conjunctival sample. Conclusions: Staphylococcus and Streptococcus were the most common conjunctival bacterial genera in this goatherd. Moraxella bovoculi was the most common single bacteria isolated from adults, and Staphylococcus equorum was the most common bacteria in kids. Mycoplasma sp. occurred infrequently at the ocular surface of adult and kid goats. A convincing association between dam‐kid vaginal–conjunctival samples was not identified.